A Shift in the Conceptual Understanding of Physics Students Through the Wright Map - Moh. Irma Sukarelawan; Ariati Dina Puspitasari; Dwi Sulisworo; Heru Kuswanto; Jumadi Jumadi (Universitas Pendidikan Ganesha, 2022)
There is limited literature reporting on the use of the Rasch model in analyzing the conceptual understanding of student temperature in Indonesia. There are 58% of Physics Education undergraduate students experience misconceptions on the topic of temperature. Therefore, this study aims to analyze students’ conceptual understanding using a two-level diagnostic instrument. Students’ conceptual understanding was administered through a survey method using a two-level misconception diagnostic instrument. The survey was conducted on 26 students (31% boys and 69% girls) ages ranging from 16 years to 19 years at a public high school. Students’ conceptual understanding of the temperature material was administered using six diagnostic items and analyzed using the Wright map. Data collection has been done online using a Google form distributed through the class WhatsApp group. Data analysis has been carried out in two stages namely, coding students’ answers, and analyzing students’ conceptual understanding. The analysis results showed a shift in the level of conceptual understanding of 50% of students. So, the Wright map provides a visualization of shifts in the level of students’ conceptual understanding of the topic of temperature.